Using an implementation science approach to enhance advance care planning practice: a community case study - Lun, Penny; Yu, Chou Chuen; Pussayapibul, Nongluck; Straus, Sharon; Goh, Siew Fong; Low, James; Tan, Woan Shin; Ng, Raymond (Frontiers in Health Services, 2025)
The process of advance care planning (ACP) can educate and prepare patients and caregivers to make better in-the-moment end of life decisions. Two nationwide studies on ACP implementation in Singapore identified gaps and barriers across various ACP practice settings, contributing to low ACP up-take and completion rates. This case study describes the key steps on how stakeholders were engaged and supported development of a quality practice guideline for ACP implementation. A knowledge exchange platform was convened through a multi-level partnership to form a workgroup tasked to translate evidence and develop quality ACP practice guidelines. Key knowledge users such as ACP implementers were engaged throughout the Knowledge-to-Action (KTA) action-cycle phase completing various associated tasks, including an e-survey conducted to prioritize barriers identified from the nationwide studies and other relevant evaluations. Prioritized barriers and their mapped Theoretical Domains Framework (TDF) were linked with relevant intervention functions and their associated implementation strategies, then contextualized into potential local applications by the workgroup. The implementation strategies were grouped into broader categories that formed domains in the practice guideline. The last action phase was engagement with ACP teams across various organizations to conduct pilot studies using implementation strategies that would facilitate quality implementation of ACP. Our quality guideline development process was supported by the KTA model that is iterative in nature with action-phases operationalized through a multi-level partnership. This is a novel approach to formulate a national quality practice guideline with lessons learned that could be applied to others pursuing similar endeavors.